Pemberian Pakan Bentuk Cramble dan Mash TerhadapProduksi Ayam Petelor - Achmad Marzuki; Bahrur Rozi (Politeknik Negeri Jember, 2018)
The purpose of this study is to determine the effect of feeding the form of crumble and mash on the production of laying hens from the pre layer phase. This research was conducted from November 11, 2015 to January 11, 2016, in laying chicken coop owned by Mr. Mahmud Kerajan Village Sumber Danti Village Sukowono District Jember District. The materials used in the study of laying pre layers (age 20 weeks) strains of Isa Brown, maize, concentrate, bran. Data analysis used was t test between (P1) chicken feed in the form of mash and (P2) chicken feed in with crumble form.The results showed that the feeding of Crumble form showed no significant difference to feed consumption ratio and feed egg ratio, and significantly different to HDP (Hen Day Production) laying hens. so it can be concluded that feeding of Crumble form can be given to increase egg production, giving advantage of difference of egg number during maintenance (age 20-28 weeks) that is 1213 grains